Early Detection and Bundled Treatment for Postpartum Hemorrhage. - Boatin, Adeline A.; Ngonzi, Joseph (The New England Journal of Medicine., 2023)
Postpartum hemorrhage is the leading cause of maternal death in developing regions, accounting for 20% of maternal deaths, most of which are preventable. This opportunity for prevention is evident by the decrease over time in the contribution of postpartum hemorrhage to maternal death in developed regions, where it accounts for8% of maternal deaths.
Detection and Bundled Treatment for Postpartum Hemorrhage.
Keywords: Detection,Bundled Treatment,Postpartum Hemorrhage